Pro Microsoft HDInsight : Hadoop on Windows - Sarkar, Debarchan (Apress, 2014)
Pro Microsoft HDInsight is a complete guide to deploying and using Apache Hadoop on the Microsoft Windows Azure Platforms. The information in this book enables you to process enormous volumes of structured as well as non-structured data easily using HDInsight, which is Microsoft's own distribution of Apache Hadoop. Furthermore, the blend of Infrastructure as a Service (IaaS) and Platform as a Service (PaaS) offerings available through Windows Azure lets you take advantage of Hadoop's processing power without the worry of creating, configuring, maintaining, or managing your own cluster. With the data explosion that is soon to happen, the open source Apache Hadoop Framework is gaining traction, and it benefits from a huge ecosystem that has risen around the core functionalities of the Hadoop distributed file system (HDFS™) and Hadoop Map Reduce. Pro Microsoft HDInsight equips you with the knowledge, confidence, and technique to configure and manage this ecosystem on Windows Azure. The book is an excellent choice for anyone aspiring to be a data scientist or data engineer, putting you a step ahead in the data mining field. Guides you through installation and configuration of an HDInsight cluster on Windows Azure Provides clear examples of configuring and executing Map Reduce jobs Helps you consume data and diagnose errors from the Windows Azure HDInsight Service